Instagram sebagai Arena Perjodohan Muslim: Ta‘Aruf Digital, Kesalehan Simbolik, dan Rekonfigurasi Intimitas - Nadiatul Maziyyah Attarwiyah; Roibin; Ahmad Barizi (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The practice of digital ta‘aruf on Instagram has become increasingly popular as an alternative form of Muslim matchmaking. However, studies specifically examining Instagram as an arena for ta‘aruf, the production of symbolic piety, and the transformation of Muslim intimacy patterns remain limited. This article aims to analyze digital ta‘aruf practices on the Instagram accounts @taaruf_an, @taaruf.uk, and @taaruf.time using Erving Goffman’s dramaturgical theory and Stig Hjarvard’s theory of the mediatization of religion.This study employs a qualitative method with a netnographic approach and visual discourse analysis. The primary data were obtained from account biographies, posts, captions, highlights, testimonials, participant codes, and registration mechanisms. The findings reveal that: (1) Instagram has become a new arena for Muslim matchmaking, shifting ta‘aruf from private spaces based on family, teachers, or community mediators into a more open, visual, and platform-structured digital space. (2) Symbolic piety is utilized as a strategy of legitimacy and trust through terms such as ta‘aruf, halal, ready for marriage, maintaining privacy, no dating, and leading to marriage. (3) Intimacy and privacy are reconfigured through short profiles, participant codes, direct messages (DMs), captions, testimonials, and platform-based selection mechanisms.This article contributes to the development of digital Islam studies by demonstrating that digital ta‘aruf is not merely the transfer of Muslim matchmaking practices to social media, but rather a process of reconstructing piety, trust, privacy, and intimacy through the platform logic of Instagram.